DIGITAL TRANSFORMATION OF PUBLIC SERVICES IN ORDER TO INCREASE CITIZEN ENGAGEMENT: A PUBLIC ADMINISTRATION THEORY APPROACH TO THE EFFECTIVENESS OF POLICE CALL CENTERS IN THE ERA OF INDUSTRIAL REVOLUTION 4.0 - Korniawan, Rommy; Zetra, Aidinil; Ariany, Ria; Andora, Hengki (Qawwam : The Leader's Writing, 2025)
This study aims to analyze the digital transformation in police call center services in Indonesia, by emphasizing the main aspects of public trust, user satisfaction, and institutional reputation. The rapid development of information and communication technology, the Indonesian National Police (Polri), continues to strive to digitalize public services to improve the effectiveness and quality of services. Polri's 110 call center service serves as a vanguard in public communication and response to security events, making it a strategic area in digital transformation. Research that has been done before to systematically examine the relationship between digitization and these three variables is still very limited. Most existing studies focus more on the technical aspects of information systems or procedural evaluation, without considering the social and institutional perspectives of digital change. Using a systematic literature review (SLR) approach based on the PRISMA protocol, this study aims to map the relevant literature and explore the linkages between digital transformation and these dimensions. PRISMA-based SLR method was chosen to provide a comprehensive overview of the dynamics of digitization in the National Police call center services. This research analyzes various studies, both from international and local contexts, to develop a more integrative conceptual framework regarding the influence of digitalization on people's perception of police institutions. This study will uncover the aspects that affect the success and challenges faced in the digitization of call center services as well as their impact on the relationship between the public and the National Police. Research shows that digitization of police call center services has significant potential in strengthening public trust, increasing user satisfaction, and improving the reputation of institutions. However, the success of this digital transformation is highly dependent on the ability of the National Police to ensure that the system implemented is responsive, transparent, and easily accessible to the public. This study also emphasizes the importance of a governance-based trust-based approach in building trust in institutions, which is relevant in the era of rapid digital interaction. It is expected that the results of this study can provide strategic recommendations for the National Police in designing a more effective digital transformation policy, as well as strengthening the legitimacy of institutions in the eyes of the public.